PENINGKATAN KOMPETENSI GURU SD DALAM MERANCANG SOAL HOTS MATEMATIKA MELALUI PELATIHAN DAN PENDAMPINGAN - Febriarsita Eka Sasmita; M.Amin M.Amin; Hanik Yuni Alfiyah; Budi Purwantiningsih (Jurnal Pengabdian Masyarakat Sabangka, 2026)
The Merdeka Curriculum emphasizes higher-order thinking skills (HOTS) as essential for students, yet its implementation in elementary Mathematics faces challenges. Teachers at SDN Gunung Sari struggle to design HOTS-based questions, particularly contextual and challenging problem-posing tasks. This community service aimed to enhance teachers’ competence through intensive training and mentoring. The program involved four stages: needs identification, conceptual and practical training, guided question development, and evaluation. Ten classroom teachers participated. Results showed notable improvement in understanding HOTS concepts and problem-posing techniques, reflected in ready-to-use HOTS Mathematics question drafts. Supporting factors included participants’ enthusiasm, relevant training materials, and hands-on methods, while inhibiting factors were limited training time and the need for ongoing mentoring. Overall, the activity successfully equipped teachers with practical skills to create high-quality assessments that promote students’ critical and creative reasoning.